Mobile learning based on natural experience approach to improve science literacy and environmental attitudes - Dian Samitra; Endang Widi Winarni (Universitas Muhammadiyah Malang, 2025)
Teacher education should foster both scientific literacy and environmental attitudes, which can be enhanced through the use of technology-based learning media. This research aims to develop a herpetofauna mobile learning based on a natural experience approach to improve science literacy and environmental attitudes teacher candidates. The research method used Research and Development with Define, Design, Development, and Disseminate (4-D) models. The research subjects were biology teacher candidates, in Lubuklinggau City, South Sumatra. The instruments for this research were material and media expert validation sheets, response questionnaires, essay questions for science literacy aspects of content and context, attitude questionnaires, and scientific process skills observation sheets. Validation data was analysed with percentage, responses were analysed descriptively, and science literacy was assessed with N-gain. Percentage analysis resulted in the validation of material experts in the medium category, and media experts in the high category. The responses for the student trials were positive. N-gain science literacy aspects of content, context, and process skills were in the high category, while science literacy in the attitude aspect was in the medium category. It can be concluded that the herpetofauna mobile learning based on natural the experience approach can increase the science literacy of teacher candidates.